(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Annabhau Sathe decided to bring awareness among the masses. Which imposed untouchability and virtually compelled the deprived lot to take recourse to criminal and filthy occupations against the British Government which imposed the Criminal Tribes Act and subjected his community to harassment and against the forces of feudalism and capitalism which exploited his community and made life unbearable. He used his art and poetic genius in educating the masses. Sathe’s use of folkloric narrative styles like powada and lavani helped popularise and make his work accessible to many communities. In Fakira, Sathe portrays Fakira, the protagonist, revolting against the rural orthodox system and British Raj to save his community from utter starvation